Answer:
a
Step-by-step explanation:
You're trying to find the distance between D and E so u use the distance formula.
sqrt (a+b-b^2)+(c-c)^2=sqrt a^2=a
(2.0×10^-4)×(3.1×10^-20)
=(2.0×3.1)×(10^4×10^-20)
=6.2×10^(-4+(-20))
=6.2×10^-24. Hope it help!
Answer:
2/6 or 1/3
Step-by-step explanation:
Nothing it is just basic mathematics
Answer:
32°, 58°
Step-by-step explanation:
Let one acute angle measure x.
The other acute angle measures 2x - 6.
The sum of the measures of the acute angles of a right triangle is 90.
x + 2x - 6 = 90
3x - 6 = 90
3x = 96
x = 32
2x - 6 = 2(32) - 6 = 58
Answer: 32°, 58°
Answer:
450miles
Step-by-step explanation:
Because she is riding at 20 miles per houre means that she ride 450 miles in 5 houre.